1973
DOI: 10.1126/science.179.4076.916
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Monoamine Oxidase Activity in Platelets: A Possible Genetic Marker for Vulnerability to Schizophrenia

Abstract: Monoamine oxidase activity in blood platelets was measured, with [(14)C]tryptamine as substrate, in 13 monozygotic twin pairs discordant for schizophrenia and in 23 normal volunteers. The monoamine oxidase activity of both schizophrenic and nonschizophrenic co-twins was significantly lower than it was for the normals, and it was highly correlated between twins. In addition, there was a significant inverse correlation between a measure of the degree of the schizophrenic disorder and the monoamine oxidase activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
50
0
1

Year Published

1974
1974
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(52 citation statements)
references
References 8 publications
1
50
0
1
Order By: Relevance
“…It was, however, important to demonstrate this in patients with schizophrenia and attempt to explain the previous findings. The proposed genetic vulnerability was related to a study in identical twins discordant for schizophrenia which showed reduced MAO activity in both co-twins, suggesting that the reduction was not secondary to schizophrenia but might represent a marker for vulnerability to schizophrenia (Wyatt et al 1973). As this study did not control for smoking, it may well be that the reduced MAO activity was due solely to either active (or passive) exposure to smoke, and not due to any genetic predisposition to schizophrenia per se.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was, however, important to demonstrate this in patients with schizophrenia and attempt to explain the previous findings. The proposed genetic vulnerability was related to a study in identical twins discordant for schizophrenia which showed reduced MAO activity in both co-twins, suggesting that the reduction was not secondary to schizophrenia but might represent a marker for vulnerability to schizophrenia (Wyatt et al 1973). As this study did not control for smoking, it may well be that the reduced MAO activity was due solely to either active (or passive) exposure to smoke, and not due to any genetic predisposition to schizophrenia per se.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced monoamine oxidase activity (MAO) was reported in 1972 (Murphy and Wyatt 1972) in the blood platelets of schizophrenic patients and they later suggested that reduced MAO activity might be a genetic marker for vulnerability to schizophrenia (Wyatt et al 1973). Despite a review of twenty-six studies convincingly demonstrating a reduction in MAO activity in platelets of chronic schizophrenic patients (Wyatt et al 1979), the finding of reduced MAO activity has remained controversial (Fleissner et al 1987).…”
mentioning
confidence: 99%
“…Studies of platelet MAO in normal families (Pandey et al 1979) and twins (Nies et al 1973) strongly suggest that the level of activity is under genetic control. Furthermore, studies in twins discordant for schizophrenia (Wyatt et al 1973;Reveley et al 1983) have shown a high correlation for low activity between the schizophrenic probands and their well (and therefore unmedicated) co-twins, suggesting that low platelet MAO cannot be completely explained as an effect of drug treatment. However, the genetic interpretation of the findings is made difficult by the fact that the mode of transmission of platelet MAO is itself unclear.…”
mentioning
confidence: 99%
“…The A type is found in human fibroblasts, while platelets contain B type which is also the form primarily found in the human brain. Platelet MAO activity has been the subject of intense interest in psychiatric research ever since Wyatt et al (1973) suggested that low activity may serve as a 'genetic marker' of vulnerability to schizophrenia. Since then, there have been many published studies on the subject, the majority of which (but by no means all) have been in agreement with the original findings (Wyatt et al 1979).…”
mentioning
confidence: 99%
“…Furthermore, some pairs may be discordant because the illness in the proband was a symptomatic schizophrenia. Studied retrospectively, however, they remain of value in the search for stable constitutional traits predisposing to schizophrenia, as exemplified in the approach of Wyatt et al (1973). Such a trait should in general distinguish schizophrenics from non-schizophrenics but should occur in both affected and unaffected members of discordant MZ pairs.…”
mentioning
confidence: 99%